Deteksi dan Edukasi Diabetes Melitus Tipe 2 di Desa Mukti Sari, Tapung, Kampar, Riau: Detection and Education of Type 2 Diabetes Mellitus People of Mukti Sari Village, Tapung, Kampar, Riau - Asni, Enikarmila; Maryanti, Yossi; Kemal, Rahmat Azhari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Type 2 diabetes is a chronic disease that is increasingly prevalent due to changes in lifestyle and economic factors. Early detection is crucial to prevent serious complications that can lead to high morbidity and mortality rates. An educational seminar and blood glucose screening were conducted in Mukti Sari Village, Tapung District, Riau Province, aimed at enhancing community knowledge about diabetes and its management. The activities included participant preparation, an interactive seminar, and blood glucose testing. Out of 76 participants aged 18-55, 57 individuals (73%) were tested; results indicated that 3 people (5.4%) had diabetes, 8 people (14.2%) were suspected of being prediabetic, and 46 people (82.1%) were normal. The prevalence of diabetes in this activity was higher than national data from 2018 (10.2%) and 2023 (11.7%). Discussions revealed that the community has good knowledge about diabetes and its complications but lacks appropriate attitudes and behaviors toward prevention, including dietary management, physical activity, and regular screenings. It can be concluded that this detection and education activity for type 2 diabetes can identify prediabetic groups in the community and inform local medical teams of the ongoing need to improve community attitudes and behaviors regarding type 2 diabetes.